2
$\begingroup$

I am stuck on this limit.

$$\lim_{n\to\infty} \sqrt[3]{n^2+5}-\sqrt[3]{n^2+3}$$

I couldn't find the limit using the basic properties of limits, since that just yields: $$\infty-\infty$$ which is undefined. Could I get any hints for finding this limit?

$\endgroup$
4
$\begingroup$

Hint: Mulitply by $$ \frac{\left(\sqrt[3]{n^2+5}\right)^2 + \sqrt[3]{n^2+5}\sqrt[3]{n^2+3} + \left(\sqrt[3]{n^2+3}\right)^2}{\left(\sqrt[3]{n^2+5}\right)^2 + \sqrt[3]{n^2+5}\sqrt[3]{n^2+3} + \left(\sqrt[3]{n^2+3}\right)^2} $$

$\endgroup$
3
$\begingroup$

You can write $\sqrt[3]{1+x}=1+\frac{1}{3}x+O(x^2)$ for $x$ near zero.

So $$\sqrt[3]{n^2+3}=\sqrt[3]{n^2}\cdot \sqrt[3]{1+3/n^2} = n^{2/3}+\frac{1}{3}\frac{3}{n^{4/3}} + O(1/n^{10/3})$$

Similarly, $$\sqrt[3]{n^2+5}=\sqrt[3]{n^2}\cdot \sqrt[3]{1+5/n^2} = n^{2/3}+\frac{1}{3}\frac{5}{n^{4/3}} + O(1/n^{10/3})$$

So $$\sqrt[3]{n^2+5}-\sqrt[3]{n^2+3}=\frac{2}{3}n^{-4/3}+O(n^{-10/3})$$


Alternatively, you can use the mean value theorem. Let $f(x)=\sqrt[3]{x}$. Then for any $n$ there is a $c_n\in [n^2+3,n^2+5]$ such that:

$$f(n^2+5)-f(n^2+3)=((n^2+5)-(n^2+3))f'(c_n)=2f'(c_n)$$

Now, show that $0< f'(c_n)\leq f'(n^2+2)$ and $f'(n^2+2)\to 0.$

$\endgroup$
2
  • $\begingroup$ Are you asking for you, or for me to clarify? I kind of deliberately left that out, but it should be fairly obvious to you, @amWhy $\endgroup$ Feb 9 '17 at 20:54
  • $\begingroup$ Okay, no, not for me. I put my "OP helmet" on when I commented, but I more than trust your pedagogy! Cheers! $\endgroup$
    – amWhy
    Feb 9 '17 at 20:55
0
$\begingroup$

One developes an intuition that as $n^2$ becomes large the $+5$ and $-3$ become negligible and the whole thing becomes but how to prove it...

Well we can is eliminate the difference of square roots by multiplying by the compliment so we can probably do the same for cube roots.

I.e. $(\sqrt[3]a - \sqrt[3]b)(\sqrt[3]a^2 + \sqrt[3]a\sqrt[3]b+\sqrt[3]b^2) = a - b$.

So $\lim (\sqrt[3]{n^2 + 5} - \sqrt[3]{n^2 + 3})=$

$\lim (\sqrt[3]{n^2 + 5} - \sqrt[3]{n^2 + 3})\frac {\sqrt[3]{n^2 + 5}^2 + \sqrt[3]{n^2 + 5}\sqrt[3]{n^2 + 3}+\sqrt[3]{n^2 + 3}^2}{\sqrt[3]{n^2 + 5}^2 + \sqrt[3]{n^2 + 5}\sqrt[3]{n^2 + 3}+\sqrt[3]{n^2 + 3}^2}=$

$\lim \frac{(n^2 + 5)-(n^2 +3)}{\sqrt[3]{n^2 + 5}^2 + \sqrt[3]{n^2 + 5}\sqrt[3]{n^2 + 3}+\sqrt[3]{n^2 + 3}^2}=$

$\lim \frac{2}{\sqrt[3]{n^2 + 5}^2 + \sqrt[3]{n^2 + 5}\sqrt[3]{n^2 + 3}+\sqrt[3]{n^2 + 3}^2}=0$

$\endgroup$
0
$\begingroup$

$\lim_{n\to\infty} \sqrt[3]{n^2+5}-\sqrt[3]{n^2+3} $

Since $a^3-b^3 =(a-b)(a^2+ab+b^2) $, $a-b =\dfrac{a^3-b^3}{a^2+ab+b^2} $.

Therefore $a^{1/3}-b^{1/3} =\dfrac{a-b}{a^{2/3}+a^{1/3}b^{1/3}+b^{2/3}} $.

Since, for $x > 0$, $1 < (1+x)^{1/3} < 1+x/3 $ (cube both sides), we have, if $u > 0$, $n^{2/3} < (n^2+u)^{1/3} = n^{2/3}(1+u/n^2)^{1/3} < n^{2/3}(1+u/(3n^2)) = n^{2/3}+u/(3n^{4/3})) $.

Therefore, if $a = n^2+u$ and $b = n^2+v$,

$\begin{array}\\ 3n^{4/3} &< a^{2/3}+a^{1/3}b^{1/3}+b^{2/3}\\ &< (n^{2/3}+u/(3n^{4/3})))^2+(n^{2/3}+u/(3n^{4/3})))(n^{2/3}+v/(3n^{4/3})))+(n^{2/3}+v/(3n^{4/3})))^2\\ &= n^{4/3}( (1+u/(3n^2))^2+(1+u/(3n^2))(1+v/(3n^2))+(1+v/(3n^2))^2)\\ &= n^{4/3}(3+(2u+u+v+2v)/(3n^2)+(u^2+uv+v^2)/(3n^2)^2\\ &= 3n^{4/3}(1+(u+v)/(3n^2)+(u^2+uv+v^2)/(3n^4))\\ \end{array} $

Therefore $$a^{1/3}-b^{1/3} =\dfrac{a-b}{a^{2/3}+a^{1/3}b^{1/3}+b^{2/3}} < \dfrac{u-v}{3n^{4/3}} $$ and $$a^{1/3}-b^{1/3} > \dfrac{u-v}{3n^{4/3}(1+(u+v)/(3n^2)+(u^2+uv+v^2)/(3n^4))}. $$

Immediately we have that $\lim_{n \to \infty} a^{1/3}-b^{1/3} =0 $.

More precisely, we also have

$$\dfrac{u-v}{3} > n^{4/3}(a^{1/3}-b^{1/3}) >\dfrac{u-v}{3}\dfrac1{1+(u+v)/(3n^2)+(u^2+uv+v^2)/(3n^4)} $$ so that $$\lim_{n \to \infty} n^{4/3}(a^{1/3}-b^{1/3}) =(u-v)/3 =2/3 $$ since $u=5, v=3$.

Note: We can get explicit bounds by using $\dfrac1{1+x} \gt 1-x $ for $0 < x < 1$ and choosing $n$ large enough compared with $u$ and $v$.

$\endgroup$
0
$\begingroup$

If you have the Mean Value Theorem available, and if you know that the derivative of $f(x)=x^{1/3}$ is $f'(x)={1\over3}x^{-2/3}$, then note that

$$\sqrt[3]{n^2+5}-\sqrt[3]{n^2+3}=2{f(n^2+5)-f(n^2+3)\over(n^2+5)-(n^2+3)}=2f'(c_n)={2\over3c_n^{2/3}}$$

for some $c_n\in(n^2+3,n^5+5)$. Clearly $c_n\to\infty$ as $n\to\infty$, so we get

$$\lim_{n\to\infty}(\sqrt[3]{n^2+5}-\sqrt[3]{n^2+3})=\lim_{n\to\infty}{2\over3c_n^{2/3}}=0$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.